Virtual planning, simultaneous dental implantation and CAD/CAM plate fixation: a paradigm change in maxillofacial reconstruction. Issue 7 (July 2020) - Seier, T.; Hingsammer, L.; Schumann, P.; Gander, T.; Rücker, M.; Lanzer, M.
Abstract: Prosthetic rehabilitation in patients undergoing reconstructive surgery using vascularized free flaps is challenging, and functional rehabilitation of the patient with a fixed prosthesis is rare. Virtually planned maxillofacial reconstruction including simultaneous dental implantation according to the prosthodontic ideal position of the implants could further enhance dental rehabilitation. The data of 21 patients undergoing fibula free flap reconstructive surgery with CAD/CAM patient-specific reconstruction plates during the years 2015–2018 were analysed, including the applicability of the virtual plan, flap survival, duration of surgery, ischemia time, simultaneous dental implantation, implant exposure, and postoperative complications. The virtual plan could be translated to surgery in all cases. In total, 76 dental implants were simultaneously placed during primary reconstruction in the 21 patients. For 38.1% of these patients, the implants could be uncovered in secondary surgery; the mean duration until exposure was 7.6 months. The implant survival rate was 97.4% (74/76). Wound infection requiring a secondary intervention occurred in 23.8% of patients during follow-up. Virtually planned reconstruction with a fibula free flap, simultaneous dental implantation, and CAD/CAM plates allows early and functional dental rehabilitation. A dental workflow should be integrated into the virtual planning, and prosthetically favourable implant positions should determine the position of the fibula segments.